The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00277-015-2438-4
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index as a prognostic factor in Asian patients treated with chemoimmunotherapy for diffuse large B cell lymphoma, not otherwise specified

Abstract: Obesity was recently reported to confer a survival advantage in diffuse large B cell lymphoma (DLBCL) among Western populations. Given ethnic differences, previous studies recommended a revision of the WHO classification of obesity for Asians. We investigated the prognostic impact of body mass index (BMI) using modified WHO criteria in a retrospective cohort of 562 Korean patients with DLBCL. Patients were categorized into five groups according to BMI: 26 (4.6 %) as underweight (<18.5 kg/m(2)), 230 (40.9 %) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
(55 reference statements)
4
18
0
Order By: Relevance
“…Hwang et al found that being underweight or severely obese has a deleterious prognostic impact in DLBCL [25]. Consistent with the findings of several previous studies [610], we found that higher BMI is an independent prognostic factor for longer PFS and OS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hwang et al found that being underweight or severely obese has a deleterious prognostic impact in DLBCL [25]. Consistent with the findings of several previous studies [610], we found that higher BMI is an independent prognostic factor for longer PFS and OS.…”
Section: Discussionsupporting
confidence: 92%
“…Most authors have used the WHO classification of obesity to distinguish between BMI groups [7, 13, 25, 26]. In contrast, Park et al [9] and Weiss et al [10] used dichotomized classification schemes with cutoffs of 20.0 and 25.0 kg/m 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [35 ]reported that modified GPS score (based on CRP and serum albumin) is a potential prognostic factor in DLBCL, and Porrata et al [39 ]found that a peripheral blood absolute lymphocyte/monocyte ratio of <1.1 during treatment independently predicted inferior OS and PFS. Others have reported that BMI is a favorable prognostic factor in DLBCL [40,41]. These findings, if confirmed by larger studies, will provide additional information on the enhancement of treatment response and survival in a large proportion of DLBCL patients.…”
Section: Discussionmentioning
confidence: 69%
“…Patient characteristics were similar to those used in our previously published article [6]. Our study cohort comprised 1021 patients with DLBCL who were treated with rituximab-based chemoimmunotherapy regimens, between January 2002 and March 2014.…”
Section: Patient Selectionmentioning
confidence: 97%